BEHAVIORAL INTERVENTION USING TOKEN ECONOMY: IMPROVING LEARNING MOTIVATION IN ELEMENTARY SCHOOL STUDENTS WITH SINGLE SUBJECT RESEARCH (SSR) METHOD - Baroroh, Nurin; Karim, Abdul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Abstract This study aims to improve elementary school students’ learning motivation through behavioral intervention using the token economy technique. The participant was a 10-year-old male student in the fourth grade. The client demonstrated low learning motivation, as reflected in academic scores below the minimum standard, frequent tardiness, passive classroom behavior, poor concentration, and a lack of persistence in completing school tasks and homework. Although the client’s IQ was within the normal range, he was unable to maximize his learning potential and often displayed behaviors that hindered his academic performance. The study employed a behavioral intervention design with the application of token economy, in which tokens were awarded for positive learning behaviors and could later be exchanged for other forms of reinforcement. The findings indicated an increase in learning motivation, evidenced by improved interest, concentration, discipline, and persistence in learning activities. These results highlight the effectiveness of token economy as an intervention strategy to enhance learning motivation in elementary school students. Keywords: Behavioral Intervention, Elementary Student, Token Economy.